PENGEMBANGAN SLOGAN KONSEP ‘GIZI SEIMBANG’ DAN GAMBARNYA (DEVELOPMENT OF SLOGAN AND ITS PICTORIAL FOR THE ‘BALANCED NUTRITION’ CONCEPT) - Heryudarini Harahap; Abas Basuni Jahari; Nurfi Afriansyah; Sri Mulyati; Tjetjep syarif Hidayat; Salimar Salimar (Persagi, 2012)
ABSTRACT Since officially released by the Ministry of Health in 1995, the Dietary Guidelines for Indonesians, ‘Pedoman Umum Gizi Seimbang’ (PUGS) is less successful to popularize the concept of 'balanced nutrition'. In contrast to the concept of 'Four Healthy Five Perfect’ (Empat Sehat Lima Sempurna), that was fortuitously at once a slogan. To obtain slogan of ‘balanced nutrition’ and their images that are easy to understand, attractive and easy to remember. The study was conducted in Cirebon, Karawang and Sukabumi district. It was a cross-sectional design. A total of seven slogan and four pictorial was developed by communication professional and researcher. Data was collected by in-depth interviews and focus group discussions (FGD). As in-depth interview informants were students of the last grade of elementary, middle and high school, adults with education elementary, junior high, high and graduate school. While informants in the FGD were cadres, teachers of elementary, junior high, and high school, as well as nutrition personnels at community health service (TPG) in each selected district. On in-depth interviews, 33 informants chose the slogan of “My Balanced Nutrition, More healthy” and 88 chose the slogan of “Eat Properly - Life Healthy”, while out of 15 FGD group, 11 FGD group chose the slogan of “My Balanced Nutrition, More Healthy”. The pictorial that selected in the FGDs and in-depth interviews are mostly circle. The slogan of “Balanced Nutrition, Healthy Life” with “circle pictorial” that might selected as one of an ‘educational message’ alternative for disseminating the concept of balanced nutrition. Kewords: Balanced nutrition, slogan, pictorial, education messages ABSTRAK Sejak dikeluarkan secara resmi oleh Departemen Kesehatan tahun 1995, Dietary Guidelines for Indonesians, yakni Pedoman Umum Gizi Seimbang (PUGS), hingga kini tergolong ‘kurang berhasil’ memasyarakatkan konsep ‘Gizi Seimbang’. Berbeda dengan konsep ‘Empat Sehat Lima Sempurna’ yang kebetulan sudah sekaligus merupakan slogan. Memperoleh slogan dan gambar konsep ‘gizi seimbang’ yang mudah dipahami, mudah diingat dan menarik. Penelitian dengan rancangan potong-lintang ini dilakukan di Kabupaten Cirebon, Karawang dan Sukabumi. Sebanyak tujuh slogan dan empat gambar dikembangkan oleh profesional komunikasi bersama dengan peneliti. Pengumpulan data dilakukan dengan wawancara mendalam dan diskusi kelompok terarah (FGD). Sebagai Informan dalam wawancara mendalam adalah siswa SD, SMP, dan SMA dari kelas terakhir, orang dewasa dengan pendidikan SD, SMP, SMA dan sarjana. Sementara informan dalam FGD diwakili oleh kader posyandu, guru SD, SMP, SMA, dan tenaga pelaksana gizi (TPG) di setiap kabupaten terpilih. Dalam wawancara mendalam, sebanyak 33 informan memilih slogan “Giziku Seimbang – Lebih Sehat” dan 88 memilih “Makan Tepat – Hidup Sehat”, sedangkan hasil FGD dari 15 kelompok FGD, 11 kelompok FGD memilih slogan “Giziku Seimbang – Lebih Sehat”. Sebagian besar gambar yang dipilih dalam FGD dan wawancara mendalam berbentuk bulat. Slogan “Gizi Seimbang – Hidup Sehat” dengan bentuk gambar bulat dapat dijadikan sebagai salah satu alternatif alat edukasi terpilih dalam memasyarakatkan konsep ‘gizi seimbang’. [Penel Gizi Makan 2012, 35(2): 110-118] Kata kunci: gizi seimbang, slogan, gambar, alat edukasi